Relativistic Compression and Expansion of Experiential Time in the Left and Right Space - Vicario, Carmelo Mario (Public Library of Science, 2008)
Time, space and numbers are closely linked in the physical world. However, the relativistic-like effects on time perception of spatial and magnitude factors remain poorly investigated. Here we wanted to investigate whether duration judgments of digit visual stimuli are biased depending on the side of space where the stimuli are presented and on the magnitude of the stimulus itself. Different groups of healthy subjects performed duration judgment tasks on various types of visual stimuli. In the first two experiments visual stimuli were constituted by digit pairs (1 and 9), presented in the centre of the screen or in the right and left space. In a third experiment visual stimuli were constituted by black circles. The duration of the reference stimulus was fixed at 300 ms. Subjects had to indicate the relative duration of the test stimulus compared with the reference one. The main results showed that, regardless of digit magnitude, duration of stimuli presented in the left hemispace is underestimated and that of stimuli presented in the right hemispace is overestimated. On the other hand, in midline position, duration judgments are affected by the numerical magnitude of the presented stimulus, with time underestimation of stimuli of low magnitude and time overestimation of stimuli of high magnitude. These results argue for the presence of strict interactions between space, time and magnitude representation on the human brain.